2007
DOI: 10.2754/avb200776020309
|View full text |Cite
|
Sign up to set email alerts
|

Combating Varroa destructor in Honeybee Colonies Using Flumethrin or Fluvalinate

Abstract: Gregorc A., M. I. Smodi‰ ·kerl: Combating Varroa destructor in Honeybee Colonies Using Flumethrin or Fluvalinate. Acta Vet. Brno 2007, 76: 309-314.Mite mortality in two apiaries, one with 32 and the other with 15 honeybee (Apis mellifera carnica) colonies, was recorded prior to and after flumethrin or fluvalinate treatments and after a control, oxalic-acid application. During the 42-and 51-day pre-treatment periods, the average daily natural mite drop was 0.04 (± 0.04) and 2.82 (± 2.19), respectively, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Comparing the relative efficacy of the used varroacides with different active ingredients (Figure 6a), the best effect was achieved for honey bee colonies from an A experimental group, and lowest for colonies from a B experimental group, where statistically significant difference was affirmed (p < 0.05; F = 6.93). Although the organic acaricides have certain advantages after repeated use, their efficacy may be inconsistent and more variable compared with synthetic acaricide formulations [24,[33][34][35][36], which is also confirmed with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Comparing the relative efficacy of the used varroacides with different active ingredients (Figure 6a), the best effect was achieved for honey bee colonies from an A experimental group, and lowest for colonies from a B experimental group, where statistically significant difference was affirmed (p < 0.05; F = 6.93). Although the organic acaricides have certain advantages after repeated use, their efficacy may be inconsistent and more variable compared with synthetic acaricide formulations [24,[33][34][35][36], which is also confirmed with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Viruses, bacteria (BT), protozoa, nematodes, rickettsiae Pathogens cause lethal infections on mites Some strains of Bacillaceae and Micrococcaceae increased mortality in in vitro tests; until now no Varroa-specific strains known Aronson et al (1986), Ball and Allen (1988), Glinski and Jarosz (1990), Tsagou et al (2004), Van der Geest et al (2000) P. Rosenkranz et al / Journal of Invertebrate Pathology 103 (2010) S96-S119 S111 natural downfall of 0.5-10 mites on the bottom board is regarded to be the threshold for a basic necessity of treatment (Arbeitsgemeinschaft der Institute für Bienenforschung e.V., 2007; Gregorc and Smodis Skerl, 2007;Liebig, 2001;Martin, 2001b). This corresponds to an absolute mite population of 2000-3000 mites which is considered as an economic threshold (Delaplane and Hood, 1999).…”
Section: Biotechnical and Biological Methodsmentioning
confidence: 98%
“…Compared to other diagnostic methods like acaricidal treatment, alcohol or detergent washes of adult bee and brood samples (Gregorc and Smodis Skerl, 2007;Rinderer et al, 2004) the measurement of the natural mite mortality is easy, cheap and fast. Depending on season and on the amount of brood, a Biological/antagonists Benign haplotype of Varroa Varroa mites' reproduction is influenced by competition for resources in multiply infested cells.…”
Section: Biotechnical and Biological Methodsmentioning
confidence: 98%
“…It has been found that this level of natural mite mortality allows the successful use of alternative mite control treatments such as oxalic acid A or thymol (Gregorc and Planinc 2005). It has also been found that in colonies with a low infestation level, fluvalinate and flumethrin were effective enough to allow colony survival during the winter (Gregorc and Smodiš Škerl 2007). The number of mites fallen from our experimental colonies during the present study indicates a moderate level of overall infestation, thus allowing the use of less effective control treatments.…”
Section: Discussionmentioning
confidence: 75%